The Language Demands of Analytical Reading and Writing at School. (April 2023) - Uccelli, Paola
Analytical writing poses particularly challenging, yet often overlooked, language demands that need attention in educational research and practice. In this article, I discuss the Core Analytical Language Skills (CALS) construct and its relevance for school reading and writing. CALS refer to the set of learners' school-relevant language resources that are of high utility to understanding analytical texts across content areas. After a brief review of the relations between mid-adolescents' language and their school reading and writing proficiencies, I offer illustrative examples of individual differences in middle-schoolers' analytical writing and CALS. I argue, on the basis of recent but extensive empirical evidence, that without understanding and addressing the immense variability in the language resources that students bring to school and the language demands of reading- and writing-to-learn tasks and texts, schools run the risk of maintaining and even exacerbating the inequalities that exist in the larger society.